Development of a Web Extended Reality (WEBXR) Based Smart Farming Simulation Game for Soybean Cultivation - Gede Sri Yuniarta; I Gede Partha Sindu; Kadek Yota Ernanda Aryanto (Lembaga Yasin AlSys, 2026)
Although digital simulation media in agriculture have received considerable scholarly attention, limited research has specifically examined the development of Web Extended Reality (WebXR)-based smart farming educational simulations to address the low regeneration of young farmers. This study aims to design and develop a WebXR-based smart farming simulation game for soybean cultivation as an interactive learning medium accessible through WebXR-enabled browsers and to evaluate its feasibility and user experience. This study employed a Research and Development (R&D) approach using the Multimedia Development Life Cycle (MDLC) model, consisting of concept, design, material collection, assembly, testing, and distribution stages. Data were collected through observation, interviews, and literature review, involving 50 student respondents from Universitas Pendidikan Ganesha through direct application testing. User experience data were obtained using the Game Experience Questionnaire (GEQ), covering In-Game and Post-Game modules. The findings show that all system functions operated properly based on black box testing, and the application was declared highly valid by content experts (1.00) and media experts (1.00). GEQ results for the In-Game components showed competence at 2.88 (high/good), sensory and imaginative immersion at 2.90 (high/good), flow at 2.37 (moderate/fair), challenge at 2.74 (high/good), tension/annoyance at 1.33 (low), positive affect at 3.21 (very high), and negative affect at 0.43 (very low). The Post-Game components showed positive experience at 3.07 (high/good), negative experience at 0.30 (very low), tiredness at 0.44 (very low), and returning to reality at 0.95 (low). The study concludes that the WebXR-based smart farming simulation game is feasible for broader implementation and effective in providing an immersive, enjoyable, and interactive learning experience for soybean cultivation. These findings contribute to agricultural education technology by demonstrating the potential of WebXR-based simulation games as modern digital learning media to support smart farming literacy and encourage youth engagement in agriculture.